Climate Change Impacts and Resilience: An Arctic Case Study - Birchall, S. Jeff; MacDonald, Seghan (2019)
Climate change is defined by the Intergovernmental Panel on Climate Change (IPCC) as an observable change in the state of the climate taking place over an extended period of time that may be caused by natural processes (i.e., volcanic eruptions) or external forces (i.e., anthropogenic changes to atmospheric composition, land use) (IPCC 2014). The United Nations Framework Convention on Climate Change (UNFCCC) takes a different approach, defining climate change as a change in climate that can be attributed directly or indirectly to anthropogenic activity and that changes the composition of Earth’s atmosphere. According to the UNFCCC, this change is in addition to observed natural climate variability over a similar period of time (United Nations 1992). Earth’s climate has naturally fluctuated over the course of history due to internal forces such as variations in ocean currents, volcanic eruptions, and atmospheric circulation. However, since the postindustrial era, anthropogenic activities have led to a large increase in the concentrations of greenhouse gases (GHG) such as carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) in the Earth’s atmosphere (IPCC 2014). These GHG emissions (largely due to the burning of fossil fuels, deforestation, and agriculture) have resulted in an increase in global average temperatures.